2001
DOI: 10.1093/emboj/20.21.5887
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic secretion of BDNF after high-frequency stimulation of glutamatergic synapses

Abstract: The protein brain-derived neurotrophic factor (BDNF) has been postulated to be a retrograde or paracrine synaptic messenger in long-term potentiation and other forms of activity-dependent synaptic plasticity. Although crucial for this concept, direct evidence for the activity-dependent synaptic release of BDNF is lacking. Here we investigate secretion of BDNF labelled with green¯uorescent protein (BDNF±GFP) by monitoring the changes in¯uores-cence intensity of dendritic BDNF±GFP vesicles at glutamatergic synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
409
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(448 citation statements)
references
References 53 publications
33
409
1
5
Order By: Relevance
“…At synapses, BDNF signaling enhances LTP, probably by cAMP-response-element-binding protein(CREB)-mediated gene expression (Ernfors et al, 2003). BDNF is also more potent in modulating active synapses (Boulanger and Poo, 1999) and as expected, its secretion occurs in active synapses (Hartmann et al, 2001;Kojima et al, 2001). In vivo BDNF infusion increases the formation of new granule cells in adult hippocampus (hilus) Figure 2 This figure depicts the molecular and biochemical events occurring in NGF-deprived hippocampal neurons, although the precise temporal sequence is only hypothesized on a timing schedule of different experiments.…”
Section: Ngf Bdnf and Synaptic Plasticitymentioning
confidence: 64%
“…At synapses, BDNF signaling enhances LTP, probably by cAMP-response-element-binding protein(CREB)-mediated gene expression (Ernfors et al, 2003). BDNF is also more potent in modulating active synapses (Boulanger and Poo, 1999) and as expected, its secretion occurs in active synapses (Hartmann et al, 2001;Kojima et al, 2001). In vivo BDNF infusion increases the formation of new granule cells in adult hippocampus (hilus) Figure 2 This figure depicts the molecular and biochemical events occurring in NGF-deprived hippocampal neurons, although the precise temporal sequence is only hypothesized on a timing schedule of different experiments.…”
Section: Ngf Bdnf and Synaptic Plasticitymentioning
confidence: 64%
“…In experiments with GFP-tagged BDNF, it was shown that high-frequency electrical stimulation could elicit release of BDNF from glutamatergic synaptic junctions (Hartmann et al, 2001). This secretion could be blocked by AMPA and NMDA antagonists and was shown to require an extracellular calcium influx (Hartmann et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There are also numerous studies showing that BDNF can elicit rapid (within minutes) presynaptic changes in synaptic activity (Lessmann, 1998;Lu and Gottschalk, 2000). For these types of synaptic plasticity, it is known that action potential firing can evoke BDNF release (Balkowiec and Katz, 2000;Hartmann et al, 2001), but it is not known whether moderate depolarization, of the type observed early during development (Ben-Ari, 2002), is also capable of inducing BDNF release. Moreover, it has not been fully shown whether BDNF actually fulfills the conditions necessary to qualify as a retrograde signaling molecule (Fitzsimonds and Poo, 1998), particularly at the single-cell level (Alger, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is produced by neurons, particularly in the hippocampus and cortex. Neuronal activity, i.e., during encoding of information, stimulates BDNF gene transcription, transport of BDNF mRNA into dendritic spines, and BDNF protein release into the synaptic cleft (Hartmann et al 2001). BDNF improves survival of cholinergic neurons of the basal forebrain, as well as neurons in the hippocampus and cortex.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%